Analisis Jumlah Pengunjung dan Retribusi (Parkir) Kawasan Wisata Religi Sunan Giri terhadap Penerimaan Pendapatan Asli Daerah (PAD) Sub Sektor Pariwisata di Kabupaten Gresik Periode 2019-2021 - Vaningsiau, Pravangasta Ajeng; Prayitno, Budi (Faculty of Economic an Business Wijaya Kusuma Surabaya University, 2023)
This study aims to analyze the factors of the number of visitors and parking fees on local revenue receipts for the tourism sub sector in sunan giri religious tourism in the period 2019 – 2021, which aims to determine how much influence the number of visitors and parking fees have on revenue receipts. Area of the tourism sub sector in sunan giri religious tourism in the period 2019 – 2021. This research ia a quantitative study, with a me in the tourism sub sector and samples from 2019 – 2021. The type of data uspopulation namely the number of visitors, parking fees. Regional original incoed is secondary data in the form of time series data. The analytical tool used in this research is multiple regression anlysis technique with an alpha 0f 0,05. The results of the study indicate that the number of visitors has a positive and significant effect on regional income in the tourism sub sector. Menwhile, parking fees have No. effect on regional original income in the tourism sub sector.